Upaya Mengatasi Miskonsepsi Siswa pada Materi Sistem Saraf Melalui Penggunaan Peta Konsep - Juhji Juhji (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The purpose of this research is to overcome student’s misconception towards nervous system material through concept map. This research applies action research as the method which consists of four steps in namely: planning, action, observation, and reflection. The subject of this research is class B of the 9th-grade students of SMPN 2 Legok Kabupaten Tangerang. The total of students is 34 students. This action research was held in October 2012. The results of research reveal that the application of concept map in nervous system learning material is able to overcome misconception problem of the students.  Cycle 1 reveals that the misconception reduced to as much as 36.5% and it increases in cycle 2 for as much as 40.6%.